2013
DOI: 10.1088/0953-8984/25/12/125504
|View full text |Cite
|
Sign up to set email alerts
|

New boron nitride structures B4N4: a first-principles random searching application

Abstract: The present investigation searched for new boron nitride (BN) polymorphs by means of first-principles simulations. The ab initio random structure searching strategy was implemented. The electronic and mechanical properties and equation of states of three new metastable BN crystal forms with equilibrium energies close to the most stable B4N4 form, c-BN, are presented. Results show either dynamically stable semiconductors or insulators, one of which is even slightly harder than c-BN. The equation of states is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Therefore, BN is used for a wide range of industrial application with harsh environments such as high temperature ceramic composites [8,9]. All BN including wurtzite BN, cubic-BN, hexagonal BN (h-BN), and BN polymorphs [10][11][12][13][14][15] are insulators and remain insulating under high level compression [8]. More recently, Zhang et al [8] discovered that three-dimensional (3D) tetragonal BN becomes metallic, which is dynamically a stable phase.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, BN is used for a wide range of industrial application with harsh environments such as high temperature ceramic composites [8,9]. All BN including wurtzite BN, cubic-BN, hexagonal BN (h-BN), and BN polymorphs [10][11][12][13][14][15] are insulators and remain insulating under high level compression [8]. More recently, Zhang et al [8] discovered that three-dimensional (3D) tetragonal BN becomes metallic, which is dynamically a stable phase.…”
Section: Introductionmentioning
confidence: 99%
“…Recently,m ore and more researchers have begun to study the polymorphs of the XN compounds (X = Al, Ga, In). [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Yang et al [6] investigated the structural, elastic,thermodynamic, electronic, and opticalp roperties of four novel compounds: Pmn2 1 -AlN, Pbam-AlN, Pbca-AlN, and Cmcm-AlN. They found that the AlN in the Cmcm phase has ab etter plasticity and also has al arger elastic anisotropyi nY oung's modulus than Pmn2 1 -AlN, Pbam-AlN, and Pbca-AlN.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more and more researchers have begun to study the polymorphs of the XN compounds (X=Al, Ga, In) . Yang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is a range of phases, usually referred to as turbostratic boron nitride (t-BN) [ 7 , 8 ], which are located between highly ordered h-BN and an amorphous material. Besides the well-known cubic diamond-like phase (c-BN) [ 9 ], wurtzite-like phase (w-BN) [ 7 ], layered graphite-like phase (h-BN or r-BN) [ 6 , 10 , 11 ], BN nanosheet [ 12 ], and BN nanotubes (BNNTs) [ 13 ], many new BN polymorphs have been experimentally prepared or theoretical predicted, including P-BN [ 14 ], BC 8 -BN [ 15 ], T-B x N x [ 16 ], Z-BN [ 17 ], I-BN [ 18 ], cT 8 -BN [ 19 ], B 4 N 4 [ 20 ], o-BN [ 21 ], bct-BN [ 22 ], zeolite-like microporous BN [ 23 , 24 ], turbostratic BN [ 25 ], and BN fiber [ 10 ].…”
Section: Introductionmentioning
confidence: 99%